Morphological diversity of 51 kenaf accessions in Nigeria (2008)
Fifty-one accessions of Hibiscus cannabinus L. were evaluated for 14 morphological parameters in Ibadan, southwestern Nigeria. The correlation matrix of the quantitative parameters was used to perform principal components (PC) analysis to understand the relative contributions of each trait to the variation observed, while Fastclus procedure was used to cluster the accession into five groups. The most widely varied traits were earliness, number of apical branches and leaf lobes per plant with 483.3, 97.9 and 60.6% coefficients of variation respectively. Correlation between fibre yield parameters and earliness was negative and significant. The first three PCs explained 66.23% of the variation, with only number of apical branches not highly weighted by any of the PC. The five clusters were distinguished by earliness, plant height, fibre yield, stem spine density, stem girth and apical branching. The variation was seen as a manifestation of environmental response in addition to the genotypic constitution. These results will aid in parent selection during breeding programmes.